2017
DOI: 10.21037/tau.2017.03.57
|View full text |Cite
|
Sign up to set email alerts
|

The impact and management of sexual dysfunction secondary to pharmacological therapy of benign prostatic hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is one of the most common genitourinary complications in men over 50 years of age and typically presents with lower urinary tract symptoms (LUTS). Classes of medications include α1-adrenoceptor blockers, 5α-reductase inhibitors, and phosphodiesterase 5 inhibitors. Today, α1-adrenoceptor blockers and 5α-reductase inhibitors are often combined to give a synergistic effect. A review of the current literature identified several adverse sexual side effects, including erectile dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…Studies with finasteride and dutasteride showed increased risks of sexual dysfunction, erectile dysfunction, ejaculation disorders, and decreased libido [21]. Also, the occurrence of erectile dysfunction is a known class effect of selective α 1 -blockers [22,23]. 0 31 69 18 Denmark 0 28 72 22 Ireland 0 45 55 22 Sweden 0 22 78 23 Belgium 41 9 50 24 UK 0 33 67 28 Hungary 43 7 50 29 The Netherlands 0 24 76 29 Austria 3 21 76 30 Switzerland 23 17 60 35 Germany 20 11 69 47 France 25 17 58 43 Greece 2 19 79 44 Czechia 14 16 70 44 Finland 0 39 61 52 Italy 4 27 69 53 Spain 15 19 65 56 Poland 9 18 73 57 Portugal 9 35 56 5-ARIs, 5α-receptor inhibitors; PI, prescription index.…”
Section: The Limits Of Standard Pharmacological Treatmentsmentioning
confidence: 99%
“…Studies with finasteride and dutasteride showed increased risks of sexual dysfunction, erectile dysfunction, ejaculation disorders, and decreased libido [21]. Also, the occurrence of erectile dysfunction is a known class effect of selective α 1 -blockers [22,23]. 0 31 69 18 Denmark 0 28 72 22 Ireland 0 45 55 22 Sweden 0 22 78 23 Belgium 41 9 50 24 UK 0 33 67 28 Hungary 43 7 50 29 The Netherlands 0 24 76 29 Austria 3 21 76 30 Switzerland 23 17 60 35 Germany 20 11 69 47 France 25 17 58 43 Greece 2 19 79 44 Czechia 14 16 70 44 Finland 0 39 61 52 Italy 4 27 69 53 Spain 15 19 65 56 Poland 9 18 73 57 Portugal 9 35 56 5-ARIs, 5α-receptor inhibitors; PI, prescription index.…”
Section: The Limits Of Standard Pharmacological Treatmentsmentioning
confidence: 99%
“…However, clinical studies in the 1990s reported that despite the amelioration of LUTS, adverse effects of BPH drug therapy began to surface. 1 These effects were noted as sexual dysfunction, which can be divided into erectile dysfunction (ED), ejaculatory dysfunction (EjD), orgasmic disorders as well as sexual desire disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse sexual side effects can occur as a result of the drug group itself or specific drugs within the group. 1 Watchful waiting is usually utilized in patients with an American Urological Association (AUA) symptom score <10. ABs bind to á 1 -adrenoceptors and act by relaxing the smooth muscles of the prostate and bladder neck to improve urine flow and facilitate urination.…”
Section: Introductionmentioning
confidence: 99%
“…Benign prostatic hypertrophy (BPH) is the most common benign tumor in males, characterized by an increased number of glandular and connective cells in the prostate and ( 1 ). BPH typically causes prostate enlargement and the secondary condition of chronic bladder outlet obstruction ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2D), characterized by persistent hyperglycemia, affects >370 million people worldwide and is a major cause of morbidity and mortality ( 8 ). T2D is a disease in which tissues are resistant to the effects of insulin and/or insulin production is insufficient to meet requirements ( 1 ). The consequence of this is an inability to regulate blood sugar, resulting in chronic hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%